1972
DOI: 10.1128/iai.6.3.335-338.1972
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Purification of Hepatitis B Antigen with Polyethylene Glycol and Polyelectrolyte 60, a Cross-Linked Copolymer of Isobutylene Maleic Anhydride

Abstract: A simple two-step procedure is described for the concentration and purification of hepatitis B antigen. The antigen is precipitated by polyethylene glycol and then adsorbed on and eluted from an insoluble polyelectrolyte, polyelectrolyte 60, which is a cross-linked copolymer of isobutylene maleic anhydride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Except, extraction effi ciency compare to the others was found to be less in potassium iodide and potassium thiocynate (0.011mg/ml and 0.050mg/ ml respectively). The same fi ndings were also reported by (Pointek et al, 2000;William et al, 1987;Friedman et al, 1987;Jih-han et al1995;DeRizzo et al 1972;Michel De Wilde et al 2001). The purity profi le on the SDS-PAGE was also confi rmed by intensity of bands after staining the gel and if their intensity was not varying much from sample to sample (results are shown in fi gure 2) the same type results have also been confi rmed by Craig et al (1987).…”
Section: Bioscience Biotechnology Research Communications Purificatiosupporting
confidence: 80%
“…Except, extraction effi ciency compare to the others was found to be less in potassium iodide and potassium thiocynate (0.011mg/ml and 0.050mg/ ml respectively). The same fi ndings were also reported by (Pointek et al, 2000;William et al, 1987;Friedman et al, 1987;Jih-han et al1995;DeRizzo et al 1972;Michel De Wilde et al 2001). The purity profi le on the SDS-PAGE was also confi rmed by intensity of bands after staining the gel and if their intensity was not varying much from sample to sample (results are shown in fi gure 2) the same type results have also been confi rmed by Craig et al (1987).…”
Section: Bioscience Biotechnology Research Communications Purificatiosupporting
confidence: 80%
“…We report herein a modification of the polyethylene glycol (PEG) procedure of De Rizzo et al (5) for the isolation of HBsAg from chimpanzee plasma. It is shown that column chromatography on hydroxylapatite separates the isolated HBsAg-associated particles into populations differing in size distribution and isoelectric points.…”
mentioning
confidence: 99%